Mulching as water-saving technique in dryland agriculture: review article - Kader, Mohammad Abdul (2021)
Agricultural water resources have been limited over the years due to global warming and irregular rainfall in the arid and semi-arid regions. To mitigate the water stress in agriculture, mulching has a crucial impact as a water-saving technique in rain-fed crop cultivation. It is important mainly for preserving soil moisture, relegating soil temperature, and limiting soil evaporation, which affects the crop yield. Mulching has many strategic effects on soil ecosystem, crop growth, and climate. Mulch insulates the soil, helping to provide a buffer from cold and hot temperatures that have a crucial activity in creating beautiful and protected landscapes. This study has accumulated a series of information about both organic and plastic mulch materials and its applicability on crop cultivation. Moreover, future research potentials of mulching with modeling were discussed to quantify water loss in agriculture.